The Effectiveness of Strip Story Learning Media on Improving Students’ Learning Outcomes in Islamic Cultural History (SKI) at MTs Ma’arif Balong Ponorogo - Arif Maulana; Nurul Azizah (STAI Ali bin Abi Thalib Surabaya, 2026)
The purpose of this study was to examine the effectiveness of Strip Story learning media in improving the learning outcomes of seventh-grade students in Islamic Cultural History at MTs Ma’arif Balong Ponorogo. This study employed a quantitative approach with a quasi-experimental design, specifically the non-equivalent control group design. The sample consisted of two classes: an experimental class taught using Strip Story media and a control class taught using PowerPoint-based learning media. The research instrument was a test. Data were analyzed using normality and homogeneity tests, followed by the Mann–Whitney U test, as the post-test data were not normally distributed. The results revealed a significant effect of Strip Story media on students’ learning outcomes. The Mann Whitney U test indicated an Asymp. Sig. (2-tailed) value of 0.000, which is less than 0.05, indicating that H₀ was rejected and Hₐ was accepted. The mean post-test score of the experimental class was 6.76, which was higher than that of the control class, with an average score of 4.17. These findings confirm that the implementation of Strip Story media has a positive effect on students’ performance in Islamic Cultural History lessons. Based on these findings, it is recommended that teachers adopt Strip Story media as an innovative instructional approach to improve the quality of learning. Students are encouraged to participate actively during lessons to achieve optimal understanding, while schools should provide institutional support for the implementation of diverse learning media. Future researchers are advised to investigate the use of Strip Story media across different subjects or educational levels to broaden the scope of related research